The Effect Of Employment Education And Training On Increasing Employees Work Productivity at PT. Sagami Indonesia - Resi Amelia (SEAN Institute, 2022)
The purpose of this study was to determine and analyze the effect of education and job training on increasing employee productivity either partially or simultaneously. The approach used in this study is an associative approach. The population in this study were all employees at PT. Indonesian Sagami. The sample in this study using the slovin formula totaling 92 employees of PT. Indonesian Sagami. Data collection techniques in this study used interview techniques, documentation studies, observation, and questionnaires. The data analysis technique in this study uses the Multiple Linear Regression Analysis Test, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. The data processing in this study used the SPSS (Statistic Package for the Social Sciences) software program version 24.00. The results of this study prove that partially and simultaneously education and job training have an effect on increasing employee productivity at PT. Indonesian Sagami.